Determinação do momento crítico de flambagem lateral com distorção em vigas mistas contínuas de aço e concreto com perfis de alma senoidal - Oliveira, Janaina Pena Soares de (2014)
The composite steel-concrete beams have been widely used in the constructions of buildings and bridges. The interaction between the steel and concrete leads to economic structures, because it is possible to take out the best of what each material can offer. In the negative moment region of continuous composite beams, the bottom flange and part of the web are compression. If the web of the steel profile doesn’t have enough stiffness to avoid the lateral flexural, the flange will displaced laterally. This instability is known as distortional lateral buckling. The procedure for verification the distortional lateral buckling of EN 1994-1-1:2004 originated the calculation method of ABNT NBR 8800:2008. But the EN 1994-1-1:2004 do not offer the expression to determine the elastic critical moment while the ABNT NBR 8800:2008 prescribes a formulation proposed by Roik, Hanswille e Kina (1990) developed for composite beams with plane web profiles. Even though the standards prescribe the verification of distortional lateral buckling for the composite beams with plane web profiles, few studies have been made about this limit state. Moreover, the ABNT NBR 8800:2008 and international standards do not approach about sinusoidal-web profiles. In this paper, was implemented elastic buckling analysis in finite element models using the software ANSYS 14.0 (2011). These models describe the behavior of distortional lateral buckling of composite beams with plane web and sinusoidalweb profiles. The numeric models were composed by steel profile, rotational spring and lateral restraint, both applied along the beam span to restrain the steel top flange. The numerical results are compared with the formulation of Roik, Hanswille e Kina (1990) and Hanswille (2002), adapted to consider the corrugation of the sinusoidal-web profile. To evaluate the formulations and consistency of the numerical model, the elastic critical moment was determined for composite beams with plane web profile. Finally, a procedure for determining elastic critical moment of composite beams with sinusoidal-web profile is proposed.